Photoinducible DRONPA‐s: a new tool for investigating cell–cell connectivity. (13th May 2018) - Gerlitz, Nadja; Gerum, Richard; Sauer, Norbert; Stadler, Ruth
Summary: The development of multicellular plants relies on the ability of their cells to exchange solutes, proteins and signalling compounds through plasmodesmata, symplasmic pores in the plant cell wall. The aperture of plasmodesmata is regulated in response to developmental cues or external factors such as pathogen attack. This regulation enables tight control of symplasmic cell‐to‐cell transport. Here we report on an elegant non‐invasive method to quantify the passive movement of protein between selected cells even in deeper tissue layers. The system is based on the fluorescent protein DRONPA‐s, which can be switched on and off repeatedly by illumination with different light qualities. Using transgenic 35S::DRONPA‐s Arabidopsis thaliana and a confocal microscope it was possible to activate DRONPA‐s fluorescence in selected cells of the root meristem. This enabled us to compare movement of DRONPA‐s from the activated cells into the respective neighbouring cells. Our analyses showed that pericycle cells display the highest efflux capacity with a good lateral connectivity. In contrast, root cap cells showed the lowest efflux of DRONPA‐s. Plasmodesmata of quiescent centre cells mediated a stronger efflux into columella cells than into stele initials. To simplify measurements of fluorescence intensity in a complex tissue we developed software that allows simultaneous analyses of fluorescence intensities of several neighbouring cells. Our DRONPA‐s system generates reproducible data and is a valuable tool for studying symplasmic connectivity. Significance statement: DRONPA‐s system is a new tool to analyse symplasmic connectivity in deeper tissue layers. Comparison of passive DRONPA‐s efflux capacities revealed strong differences in cellular connectivity between the cell layers of the root tip of Arabidopsis thaliana .